Segementasi Potential Entrepeneur Dan Aspek-Aspek Mempengaruhinya Di Indonesia: Pemanfaatan Data Global Entrepreneurship Monitor - Deltha Airuzsh Lubis (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
Entrepreneurial activity is considered as one of the solutions in reducing the unemployment rate because it can absorb labor and encourage national economic development. Several Asian countries have experienced economic changes over the last three decades which were marked by an increase in the number of business activities and business output with the direction of achievement in line with the pace of economic growth. Meanwhile, novice business actors at the national level are still relatively low. Based on this, it is interesting to explore the segmentation of potential entrepreneurs and startups and the aspects that influence it by utilizing GEM data. The results showed that with the Chi-Squared Automatic Interaction Detection (CHAID) method, people living on the island of Java with an age range of 35-44 years with the status of working at home, or working full time or part time, are likely to become potential entrepreneurs around 59.7%. The results of the logistic regression show that internal factors (career choice, business skills and knowledge, and fear of failure in entrepreneurship), and external factors (people around who are also entrepreneurs, the first opportunity to start a business, media showing business success stories, and respectable social status of business people) affects the increase in potential entrepreneurs.